2016
DOI: 10.1111/1750-3841.13566
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Sequencing of Viable Microbial Communities in Raw Pork Subjected to a Fast Cooling Process

Abstract: This study aimed to investigate the effect of the fast cooling process on the microbiological community in chilled fresh pork during storage. We established a culture-independent method to study viable microbes in raw pork. Tray-packaged fresh pork and chilled fresh pork were completely spoiled after 18 and 49 d in aseptic bags at 4 °C, respectively. 16S/18S ribosomal RNAs were reverse transcribed to cDNA to characterize the activity of viable bacteria/fungi in the 2 types of pork. Both cDNA and total DNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…counts, Bronchothrix spp. counts and Enterobacteriaceae counts were performed according to the methods described as Yang et al (2017). Briefly, at each sampling date, 10 g of sample was aseptically removed into stomacher bags containing 90 mL sterile 0.1% peptone water, and then was mixed in a blender.…”
Section: Bacterial Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…counts, Bronchothrix spp. counts and Enterobacteriaceae counts were performed according to the methods described as Yang et al (2017). Briefly, at each sampling date, 10 g of sample was aseptically removed into stomacher bags containing 90 mL sterile 0.1% peptone water, and then was mixed in a blender.…”
Section: Bacterial Countsmentioning
confidence: 99%
“…Due to the influence of both enzymatic and microbial reactions, fresh beef is highly perishable and has quite short storage life postmortem under chilled storage (4-5 °C) (Magrinyà et al, 2015). Spoilage of raw beef during production and sales will result in a waste problem and potential microbial safety hazards for the public health (Yang et al, 2017). Consequently, the food safety and food transportation efficiency of fresh beef is of major concern to consumers and meat industries.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that bacon is naturally produced without any starter cultures, these bacteria may emerge from raw meats or processing environment. Some reports have shown that raw meat may be the origin of microbes in bacon preparation ( Doulgeraki et al, 2012 ; Yang et al, 2017 ). In a previous study, Acinetobacter and Pseudomonas were also found to be dominant genera in the fresh pork samples ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that raw meat may be the origin of microbes in bacon preparation ( Doulgeraki et al, 2012 ; Yang et al, 2017 ). In a previous study, Acinetobacter and Pseudomonas were also found to be dominant genera in the fresh pork samples ( Yang et al, 2017 ). Three genera ( Aeromonas , Shewanella , and Flavobacterium ) dominated the fresh and chilled fresh pork samples ( Yang et al, 2017 ), were present only with a relative abundance below 0.001 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the bacterial and fungal communities, the bacterial 16S rRNA gene was amplified using the primers 338F (5 0 -ACTCCTA CGGGAGGCAGCAG-3 0 ) and 806R (5 0 -GGACTACHVGGGTW TCTAAT-3 0 ) (Fierer et al, 2005) and the fungal 18S rRNA gene was amplified using the primers 0817F (5 0 -TTAGCATGGAATAATRRAA TAGGA-3 0 ) and 1196R (5 0 -TCTGGACCTGGTGAGTTTCC-3 0 ) (Yang et al, 2017). The purified PCR product sequencing was performed on an ABI 3730XL DNA sequencer.…”
Section: Determination Of Bacterial and Fungal Abundances And Communitiesmentioning
confidence: 99%